Rosettes in cutaneous angiosarcoma: a new dermoscopic clue - Larissa Daniele Machado Góes; José Genival Alves de Macedo; Manoel Benjamim de Almeida Barbosa; Tayenne da Silva Gomes; Lisandro Ferreira Lopes (Sociedade Brasileira de Dermatologia (SBD), 2022)
Cutaneous angiosarcoma is a rare cancer with a poor prognosis that affects mainly elderly men. It is related to chronic exposure to sunlight, chronic lymphedema, and procedures using radiation. We report a case of a 62-year-old man with a progressively growing violaceous tumor in the left temporal region. Dermoscopy showed erythematous areas of diferent shades, pseudo-follicular openings structures, and rosettes. The biopsy and the immunohistochemical study confirmed the diagnosis of cutaneous angiosarcoma. The patient is currently undergoing chemotherapy treatment in the oncology service with significant improvement of the lesion.